IDENTIFIKASI FUNGSI BAHASA YANG BERBASISKAN KEARIFAN LOKAL PADA MATERI PEMBELAJARAN BAHASA INGGRIS PERHOTELAN BIDANG TATA HIDANG - Ni Made Ayu Sulasmini; Nyoman Gede Astina (Institut Pariwisata dan Bisnis Internasional, 2018)
Empirical studies find that services affect tourist satisfaction. There are involvement of several aspects in the service including physical quality and staff behavior (Ekinci et al., 2008). Services that have a high level of contact with customers require interaction between service providers and customers which are the determinants to satisfaction. Local wisdom should be reflected in all aspects of service at the hotel, including the use of English.Teaching English in hospitality institutions applies ESP (English for Specific Purposes) learning patterns. English in the Food and Beverage service for example,Â is adjusted to the sequence of service. The language function, will follow the service sequence in the restaurant environment. Considering that local wisdom is a determining factor in satisfaction in service, this study aims to identify the use of Balinese language in the service area in restaurants. This study will use observation and interviews in inventorying the language function, as well as documentation studies to insert the value of local wisdom.The use of Balinese language was found at the time of thanking the guest and farewell, even though it was not yet included in the SOP. At the same time, there was no found in the Balinese language teaching in STPBI. This study recommends that these utterances be introduced during the Teaching and Learning English Language.Â Keywords: Service, Local Wisdom, Language Function, Procedure.